The influence of age and distance from aquatic habitats on the pyrethroid resistance phenotypes of Anopheles funestus mosquitoes in South-Eastern Tanzania - Pinda, Polius (My University, 2022)
Background: Malaria transmission risk can be unevenly distributed due to various environmental factors such as the distribution of mosquito breeding habitats and human dwellings, mosquito-related factors such as blood-feeding behaviours, susceptibility to insecticides, dispersal range, age and non-random host selection thus, shaping the effectiveness of interventions used. This study investigated how the age of Anopheles funestus and their susceptibility to insecticides used for vector control vary by distance from their aquatic habitats, and how these correlations may inform vector control strategies in southern Tanzania. Methods: Adult female An. funestus were collected in houses located at 50-100 m, 150-200 m or over 200 m from the nearest known aquatic habitats. The mosquitoes were exposed to 1× (the standard diagnostic dose), 5× (five times the diagnostic dose) and 10× (ten times the diagnostic dose) of either deltamethrin or permethrin, or to the synergist, piperonyl butoxide (PBO) followed by the pyrethroids, then monitored for 24hr mortality. Ovaries of exposed and nonexposed mosquitoes were dissected to assess parity status as a proxy for age. Emergent adults from larval collections in the same villages were exposed to the same insecticides at either 3-5 days, 8-11 days or 17-20 days old. Generalized linear mixed-effects models were used to compare the 24hr-mortality for candidate insecticides by age and distance. Findings: Mosquitoes collected nearest to the aquatic habitats (50-100 m) had the lowest mortality compared to those from other distances (150-200 m, over 200 m); with a maximum of 51% mortality at 10× permethrin. For the age-synchronized emergent mosquitoes collected as larvae, the highest mortalities were observed at the oldest age (17-20 days) when exposed at 1x doses. At 10× permethrin and deltamethrin doses, 99% and 76% mortality was observed among the 8-11 day-olds compared to 56% and 58% among 3-5 day old mosquitoes respectively. Preexposure to PBO restored the potency of insecticides on mosquitoes. The percentage of parous mosquitoes increased with distance from aquatic habitats, thus indicating the increased age of mosquitoes with distance from aquatic habitats. Conclusion: Older An. funestus and those collected farthest from the aquatic habitats (near the centre of the village) were more likely to die from exposure to pyrethroids than younger ones and those caught nearest to the habitats. Additional studies should investigate whether insecticidebased interventions would remain sufficiently effective in areas of widespread pyrethroid resistance by killing the older, less resistant and potentially-infective females or if fine-scale targeting of insecticide-based interventions such as IRS (e.g. by prioritizing households farthest from habitats) would be optimal.
A research report submitted in Partial Fulfilment of the requirements for the Degree of Masters of Science in Epidemiology (Infectious Disease Epidemiology) to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2022